Outcomes of haploidentical hematopoietic stem cell transplantation in adults aged 60 and over: a systematic review and meta-analysis - Khamis, Mohamed M.; Cheikh, Israa Ahmad; Babic, Aleksandar; Kunwor, Ranju (Frontiers in Hematology, 2026)
BackgroundHaploidentical hematopoietic stem cell transplantation (HSCT) has become a viable option for older adults with hematologic malignancies lacking matched donors. However, outcomes in patients aged ≥60 years vary widely, with reported 2-year overall survival (OS) ranging from 15% to 74%. This systematic review and meta-analysis aimed to estimate pooled survival outcomes and identify factors contributing to outcome heterogeneity in older recipients of haploidentical HSCT.MethodsA comprehensive systematic literature search was conducted across PubMed, Google Scholar, and Cochrane databases from inception to April 30, 2025, following PRISMA guidelines. Studies enrolling adults aged ≥60 years undergoing haploidentical HSCT with reported OS, non-relapse mortality (NRM), or relapse incidence at 1-, 2-, or 3-years were included. Meta-analyses were performed using DerSimonian-Laird random-effects models. A composite “High-Impact Trio” risk score was developed based on the prevalence of active/refractory disease, high-risk cytogenetics, and impaired performance status to explore heterogeneity through subgroup analyses and meta-regression.ResultsSixteen studies (18 cohorts; 1,268 patients) were analyzed. Pooled survival estimates were: 1-year OS 62% (95% CI, 56–68%), 2-year OS 53% (95% CI, 46–60%), and 3-year OS 45% (95% CI, 38–52%). Three-year NRM and relapse incidence were 28% (95% CI, 23–34%) and 32% (95% CI, 25–40%), respectively. Significant heterogeneity was observed (I² = 71–82%); the risk score explained 39–60% of between-study variability and correlated with OS and NRM (P<0.05).ConclusionHaploidentical HSCT offers competitive survival outcomes in selected older patients, though prognosis remains strongly influenced by baseline risk factors. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251013617.